The Impact of Resource Allocation and Purchasing Reforms on Equity - Belli, Paolo Carlo (World Bank, Washington, DC, 2013)
This paper introduces a conceptual framework to investigate the equity consequences of resource allocation, strategic purchasing and payment system reforms (RAP) in health, and reviews the empirical literature that has analyzed the impact of these reforms on equity. In the first part, the paper reviews the existing evidence on the distribution of health and health care utilization across socio-economic groups in developing countries. Such evidence shows a striking consistency in the association between poverty and poor health, and that the distribution of health benefits across socio-economic groups is highly unequal, favoring the wealthier segments of the population. At the same time it shows that the issue of quality of services is as important as the issue of their accessibility. Then the paper addresses the meaning of equity in health care: we argue that the concept of equity and that of an equitable distribution of resources in health are not as straightforward as they appear. In the second part, the paper reviews the core elements of RAP reforms, and it presents a survey of the empirical literature that has investigated the impact of RAP reforms from an equity perspective. We argue that some RAP reform components, such as the new resource allocation mechanisms, bear a strong pro-poor potential, but that other components can lead to the emergence of trade-offs between conflicting objectives, such as efficiency and equity. For instance, the new purchasing contracts and payment systems devised to enhance efficiency can create adverse equity effects. Conceptually, these trade-offs are significant and operating at several levels.